Fenomena Kejahatan Deepfake Pornografi dalam Perspektif Roscoe Pound: Penelitian - Renjana Mantri Laras Hadi Daulay; Rosmalinda; Agusmidah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The purpose of this study is to examine the phenomenon of deepfake pornography crime from Roscoe Pound's perspective. This study uses a qualitative empirical method with a legal and conceptual approach. The data obtained includes primary and secondary data, where primary data is generated through observation, including non-participant observation. Meanwhile, secondary data is obtained from books on legal sociology, Roscoe Pound's writings, scientific journals, laws and regulations, and relevant scientific articles. The data collection technique was conducted through literature/documentation studies. The data analysis technique used qualitative-descriptive data analysis, namely analysis by linking the phenomenon of deepfake pornography crime with Roscoe Pound's theoretical framework. The results of the study show that, first, deepfake pornography is a criminal phenomenon involving the manipulation of images or videos of other people without permission to produce pornographic content. Second, regulations governing deepfake pornography include the TPKS Law, PDP Law, and ITE Law. However, these three laws are still considered unable to provide comprehensive legal benefits, meaning that these regulations still have shortcomings that need to be addressed, such as legal loopholes, unclear articles that require interpretation, and effective law enforcement. Third, According to Roscoe Pound, the law in deepfake pornography cases should act as a tool of social control that prioritizes real benefits in order to protect privacy and restore victims' rights fairly.